Soft x-rays from plasma focus / Chaivity Silawatshananai - Chaivitya Silawatshananai (Prince of Songkla University, 2024)
The temporal characteristics of the X-ray emission in a small 3 kJ plasma focus of Mather type are investigated when operating in deuterium, argon and nitrogen gases. The soft X-ray emission is detected with a five channels BPX-65 PIN-diode spectrometer, looking axially into the focussing region. Results show that soft X-ray emission coincides with successive plasma compressions. Some spectra contain the copper K line radiation. This strong copper line radiation is due to electron beam-anode interaction or focussing effect of copper vapour contaminated plasma. Electron temperatures in argon and deuterium plasmas are inferred from the ratio of x-ray intensities to be 1.5 KeV and ~10 KeV respectively.